2017
DOI: 10.1177/1062860617738327
|View full text |Cite
|
Sign up to set email alerts
|

Physician Perceptions of Performance Feedback in a Quality Improvement Activity

Abstract: Physician performance and peer comparison feedback can affect physician care quality and patient outcomes. This study aimed to understand family physician perspectives of the value of performance feedback in quality improvement (QI) activities. This study analyzed American Board of Family Medicine open-ended survey data collected between 2004 and 2014 from physicians who completed a QI module that provided pre- and post-QI project individual performance data and peer comparisons. Physicians made 3480 comments … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
32
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(32 citation statements)
references
References 32 publications
(36 reference statements)
0
32
0
Order By: Relevance
“…For example, the addition of a measure requires changes to the reports form and content to display new information. Refinements from understanding the user may relate to user preferences or ability to read a type of chart [24] or user expectations for meaningful comparators [25].…”
Section: Refine Measuresmentioning
confidence: 99%
“…For example, the addition of a measure requires changes to the reports form and content to display new information. Refinements from understanding the user may relate to user preferences or ability to read a type of chart [24] or user expectations for meaningful comparators [25].…”
Section: Refine Measuresmentioning
confidence: 99%
“…Several studies have shown that the comparison with peers has a positive effect on behavioral change [4][5][6][7][8]. Whether regression towards the mean of peers is good, however, depends on the excellence of the peers' practice, which may not always be taken for granted.…”
Section: Limitationsmentioning
confidence: 99%
“…The feedback that compares the performance of clinicians with their peers is even more important for the behavioral change of clinicians [4][5][6][7][8]. Meeker et al [5] found peer comparison to be the most efficient feedback method to minimize inappropriate antibiotic prescriptions.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The study team conducted a study across a wide range of innovation models to learn what approaches have worked well to provide claims-based data to model participants and what could be improved going forward. Prior literature addressing confidential feedback data have tended to focus on reporting to physicians, [5][6][7][8][9][10][11] especially primary care physicians, [8][9][10][11] and, more recently, accountable care organizations (ACOs). 11,12 This study makes an important contribution by evaluating the provision of claims-based data to a much broader range of organizations participating in 18 CMS models.…”
mentioning
confidence: 99%